Microbial shelf life of chub-packaged ground beef from four large U.S. processing plants - P.E. Peters; S.D. Gamage; J.B. Luchansky; Randall K. Phebus (Kansas Agricultural Experiment Station Research Reports, 1998)
Ten pound chubs of coarsely ground beef of two different lean:fat specifications (73:27 and 81:19) were stored at three temperatures (34, 38 or 45 ÌŠF) to monitor the effects of storage temperature on microbial condition of the product. Ground beef from four U.S. plants was tested (2 trials each), and microbial analyses were conducted on storage days 0, 6, 10, 14, and 18 using seven different media to estimate counts of total aerobic and anaerobic, lactic acid bacteria (LAB), and Gram-negative bacteria. Bacterial counts for a given culture medium were similar among plants and meat types. At day 10, total mi crobial counts from chubs stored at 38 or 45 ÌŠF were approximately 8 log10 CFU/g, whereas total counts from chubs stored at 34 ÌŠF were approximately 4.5 log 10 CFU/g (4 log=10,000, CFU is colony forming units). Regardless of storage temperature and meat type, LAB predominated. Growth of gram-negative enteric bacteria was delayed in chubs stored at 34 ÌŠF throughout the 18 day study, whereas counts increased in chubs stored at 38 or 45 ÌŠ F.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen& #x27; s Day; 1998; Beef; Ground Beef; Shelf life; Meat spoilage; Microbiology